An intelligent ZIF-8-gated polydopamine nanoplatform for in vivo cooperatively enhanced combination phototherapy. Issue 6 (10th January 2020) - Feng, Jie; Yu, Wenqian; Xu, Zhen; Wang, Fuan
Abstract : The extreme complexity and heterogeneity of fatal tumors requires the development of combination phototherapy considering the limited therapeutic efficiency of conventional monomodal photodynamic therapy (PDT) or photothermal therapy (PTT). Abstract : The extreme complexity and heterogeneity of fatal tumors requires the development of combination phototherapy considering the limited therapeutic efficiency of conventional monomodal photodynamic therapy (PDT) or photothermal therapy (PTT). However, tumor-specific drug administration and the accompanying hypoxia-restrained PDT present the main obstacles for executing an efficient combination phototherapy. Developing a highly biocompatible, tumor-specific, near infrared absorbing, and oxygen (O2 )-evolving multifunctional nanoplatform is thus crucial for an effective PDT-based combination therapy. In this contribution, a multifunctional ZIF-8-gated polydopamine nanoparticle (PDA) carrier was synthesized for simultaneously delivering a photosensitizer and a catalase (CAT) into tumor cells, thus realizing a cooperatively enhanced combination photodynamic and photothermal therapy, as systematically demonstrated in vitro and in vivo . The ZIF-8 gatekeeper facilitates the simultaneous and effective delivery of these functional payloads, and the subsequent tumor acidic pH-stimulated drug release. This leads to a significant improvement of combination efficacy by ameliorating tumor hypoxic conditions since the CAT-mediated self-sufficient O2 generation could substantially promote an efficient PDT operation. In addition, this nanoplatform can effectively convert near infrared photoradiation into heat, resulting in thermally induced elimination of cancerous cells. As an intelligent multi-mode therapeutic nanosystem, this inorganic/organic hybrid nanosystem showed great potential for accurate cancer diagnosis and immediate therapy.